Governance of the Merah Putih Village Cooperative: Review of Membership Policies, Governance, and Community Participation - Andi Armayudi Syam; Andi Ahmad Andi Ahmad Malikul Afdal; Jusran (Universitas Muhammadiyah Makassar, 2025)
The Red and White Village/Subdistrict Cooperative is a new government policy initiative aimed at strengthening village economies through the spirit of mutual cooperation (gotong royong). This article presents a recent study on membership policies, governance, and community participation within the Red and White Village Cooperative. The research adopts a qualitative descriptive approach, employing a literature review of scholarly journals and an analysis of relevant policy documents. The findings indicate that the cooperative’s membership policy is inclusive of village residents; however, it faces challenges in encouraging active participation from more than half of the population as members. Cooperative governance is implemented democratically through Members’ Meetings, and the principles of transparency and accountability have begun to be applied, although managerial capacity at the local level remains limited. Member participation is shown to play a strategic role in the success of the cooperative—members act not only as beneficiaries but also as owners and managers, making their involvement in decision-making processes crucial. The main challenges identified include limited managerial competence among board members, potential overlap with Village-Owned Enterprises and the risk of dependency on central government support. Through strengthening member capacity, improving the quality of governance, and adopting a participatory approach, the Red and White Village Cooperative has the potential to become a model of independent, equitable, and sustainable village economic empowerment